2015
DOI: 10.1007/s12053-015-9386-7
|View full text |Cite
|
Sign up to set email alerts
|

Analysing the impact of ENERGY STAR rebate policies in the US

Abstract: In this paper we estimate the impact of rebate policies in various US states on the sales share of ENERGY STAR household appliances. We use annual ENERGY STAR sales data for clothes washers, dishwashers, refrigerators and air conditioners from 2001 to 2006 and the variation in the coverage of rebates across US states and over time to identify the impact of rebate policies. We use, at first, a difference-in-differences approach to estimate this impact. Then, we take into account the possibility of rebate polici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…Policy makers typically choose to apply these instruments to incentivise specific product purchases (Galarraga et al 2016) and to support certain technologies (Bertoldi et al 2013). Empirical findings show that financial incentives increase energy efficiency investment (Datta and Filippini 2016;Datta and Gulati 2014;Markandya et al 2009), however they are also associated with two main drawbacks: the free-rider problem and the rebound effect 5 . Researchers in the field have investigated that households and industries are likely to free ride on financial support provided (e.g.…”
Section: Financial Incentivesmentioning
confidence: 99%
“…Policy makers typically choose to apply these instruments to incentivise specific product purchases (Galarraga et al 2016) and to support certain technologies (Bertoldi et al 2013). Empirical findings show that financial incentives increase energy efficiency investment (Datta and Filippini 2016;Datta and Gulati 2014;Markandya et al 2009), however they are also associated with two main drawbacks: the free-rider problem and the rebound effect 5 . Researchers in the field have investigated that households and industries are likely to free ride on financial support provided (e.g.…”
Section: Financial Incentivesmentioning
confidence: 99%
“…Studies investigating the success of policies implemented, such as the ENERGY STAR in the U.S. or A-G energy labels in Europe, show that financial incentives (subsidies), energy audits, minimum energy performance standards (MEPS), energy literacy and reduced value added taxes for EE technologies contribute positively to the uptake of energy efficient appliances and replacement of old equipment (De Almeida et al 2011, Mills and Schleich 2012, Brounen et al 2013, OECD 2013, Murphy 2014, Krishnamurthy and Kriström 2015, Datta and Filippini 2016, Zhou and Yang 2016, Girod et al 2017).…”
Section: Literature Reviewmentioning
confidence: 99%
“…In terms of incentive programs, the results suggested that rebate policies of energy stars increased the sales share of energy-efficient appliances, ranging from 3.3% to 6.6% [51]. Filippini et al indicated that financial incentives played a significant role in lowering energy demand [49].…”
Section: Literature Reviewmentioning
confidence: 99%